2010
DOI: 10.1063/1.3514125
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric and ferroelectric response of compositionally graded bilayer and trilayer composites of BaTiO3 and 0.975BaTiO3–0.025Ba(Cu1/3Nb2/3)O3

Abstract: In this paper, we report the dielectric and ferroelectric response of compositionally graded bilayer and trilayer composites consisting of BaTiO 3 ͑BT͒ and 0.975BaTiO 3 -0.025Ba͑Cu 1/3 Nb 2/3 ͒O 3 ͑BTBCN͒. Two types of graded bilayer samples were synthesized, one with same thickness of BT and BTBCN while other with different layer thicknesses. The graded trilayer sample consisted of BT layer sandwiched between two BTBCN layers of equal thickness. Scanning electron microscopy and transmission electron microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…9 We do not expect change in stoichiometry of the materials or signi-cant weight loss aer sintering process due to absence of volatile elements. All the sintered pellets were found to have more than 95% of theoretical density.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 We do not expect change in stoichiometry of the materials or signi-cant weight loss aer sintering process due to absence of volatile elements. All the sintered pellets were found to have more than 95% of theoretical density.…”
Section: Methodsmentioning
confidence: 99%
“…Magnetically diluted Cu 2+ centers (3d 9 ) with an electron spin S ¼ 1/2 can be represented by a spin Hamiltonian:…”
Section: +mentioning
confidence: 99%
“…11 The value of ␣ obtained for KNN single crystals is on the higher side and accounts for the square shape of ferroelectric loops. 10,11 The ferroelectric response of the pure crystals was lower than that expected for the ͗100͘ oriented orthorhombic phase. In order to understand this observation, dynamic hysterics analysis based on ͑⌽ 2 ͒ 2 model was conducted on these crystals.…”
mentioning
confidence: 99%
“…Using this approach, Ota et al [7] produced Ba1-xSrxTiO3-based capacitors with a temperature-independent electrical permittivity. And Maurya et al [8] showed that layered BaTiO3/0.975BaTiO3-0.025Ba(Cu1/3Nb2/3)O3 ceramics could be employed to better understand hysteresis dynamics to tailor their piezoelectric and ferroelectric properties.…”
Section: Introductionmentioning
confidence: 99%